Penerepan Metode Certainty Factor Dalam Mendiagnosa Dini Gangguan Pemusatan Perhatiandan Hiperaktivitas Pada Anak - Suhariono Jaya (Buletin Ilmiah Informatika Teknologi, 2022)
Lack of public knowledge about abnormal behavior results in abnormal behaviors that exist and appear to be often misunderstood, and it is not uncommon for people with abnormal behavior to be treated inhumanely. Not only in adults, abnormal behavior can also be experienced by children. One form of abnormal behavior is attention deficit disorder in children. The purpose of this study is to create an expert system application that runs on the Windows operating system that can diagnose Concentration and Hyperactivity Disorder in Children by providing diagnostic results based on the level of confidence in the symptoms suffered by the patient using the Certainty Factor method. The application of the Certainty Factor method can strengthen the resulting diagnosis because the system has a value so that the level of certainty or level of confidence is more accurate. From the system designed and the test results manually obtained an accuracy value of 0.9676 or if it is presented the value becomes 96.76% for Combine symptoms (Inattentive, Hyperactive / Impulsive and Impulsive).